UTSMAN BIN AFFAN: NEPOTISM AND REBELLION - Sefrianti, Riski; Afrizal, Afrizal; Sawaluddin, Sawaluddin (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to determine the process of exposing the caliph Usman Bin Affan who was rumored to be nepotism until the rebellion occurred during the caliphate of Uthman bin Affan (24-36 AH/644-656 AD). The main focus of the research is to understand how nepotism and rebellion occurred during the reign of Uthman Bin Affan. Research methods for research libraries or literature such as history books, journal articles and other related documents using content analysis. The results of the research show that during Uthman bin Affan's caliphate, after briefly explaining the personalities of people close to Caliph Uthman who held important positions in his government, it can be concluded that their appointment was a natural thing. This is because they have proven worthy of holding that position. They have the credibility to hold office, not just because of elements of nepotism. Meanwhile, the rebellion was caused by Abdullah bin Saba who sought ways to divide the Muslims, such as by indoctrinating heretical ideas. Slander was spread to overthrow the leadership of Uthman Bin Affan.